2012
DOI: 10.1007/s12010-012-9595-x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Microbial Cellulose by a Bacterium Isolated from Fruit

Abstract: This study presents the production of bacterial cellulose (BC) by a bacterium isolated from a rotten fruit and its process optimization. Here, isolation and screening of potent cellulose producers were carried out from different natural sources, viz., soil, rotten fruits, and vegetables and vinegar. A total of 200 bacterial isolates were obtained, which were screened for cellulose production using Hestrin-Schramm medium. A novel and potent cellulose-producing bacterium was newly isolated from a rotten fruit an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 43 publications
3
35
0
3
Order By: Relevance
“…For instance, it was revealed that the increase in cell inoculum concentration over 5% (v/v) lowers the BC yield [42]. A similar conclusion done by other researches experimentally revealed how the amount of cell inoculum influences the BC production [43]. It appeared that when the inoculum concentration was decreased from 6-4% (v/v), the BC accumulation was increased, and further increasing or decreasing the inoculum from 4%, a decline in BC production was observed.…”
Section: Discussionsupporting
confidence: 70%
“…For instance, it was revealed that the increase in cell inoculum concentration over 5% (v/v) lowers the BC yield [42]. A similar conclusion done by other researches experimentally revealed how the amount of cell inoculum influences the BC production [43]. It appeared that when the inoculum concentration was decreased from 6-4% (v/v), the BC accumulation was increased, and further increasing or decreasing the inoculum from 4%, a decline in BC production was observed.…”
Section: Discussionsupporting
confidence: 70%
“…; Jahan et al . ), whereas some researches indicated pH 4–6 as the optimum pH range (Fontana et al . ; Masaoka et al .…”
Section: Resultsmentioning
confidence: 99%
“…Besides that, most of the biocellulose‐producing bacterial strains were obtained from fruits such as apple, orange, tomato, grape and wild lemon (Jahan et al . ; Tanskul et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…A new bacterium (Gluconacetobacter sp. F6) was isolated from rotten fruit and the conditions required to obtain optimum cellulose from the fruit waste were studied [12Jah]. In addition to rotten fruit, soil, vegetables, and vinegar were also studied as potential sources for bacterium.…”
Section: Agricultural Residues As Feedstocks For Production Of Bactermentioning
confidence: 99%
“…In addition to rotten fruit, soil, vegetables, and vinegar were also studied as potential sources for bacterium. A cellulose yield of 4.5 g/l was obtained under the optimum conditions of pH 6, temperature of 30 C, and using glucose as the carbon source [12Jah]. A thick leathery pellicle formed during production of grape wine was studied for its structure and properties and identified as bacterial cellulose from the Gluconacetobacter sp.…”
Section: Agricultural Residues As Feedstocks For Production Of Bactermentioning
confidence: 99%